A Systematic Review of Growth Mindset Interventions Targeting Youth Social-Emotional Outcomes - Jiang, Xu; Mueller, Christian E.; Paley, Netanel (School psychology review, 2024)
Research on the growth mindset interventions (GMIs) on nonacademic outcomes is burgeoning. The present systematic review aims to evaluate the effects of GMIs on social-emotional outcomes among school-aged children and adolescents. Using the PRIMSA guidelines, our search across three electronic databases (PsycINFO, ERIC, and PubMed) yielded an initial identification of 1057 records. Inclusion criteria include publication format, language, participant age range, and intervention purpose, focus and components. Risk of bias was analyzed at the study level using a list of research quality indicators and across studies by comparing nonpeer reviewed versus peer reviewed publications. Our final sample yielded 13 papers including 14 studies. The findings from these studies were extracted to examine research quality, sample characteristics, intervention content, and intervention effects of the GMIs. Results showed despite that study quality, samples, and intervention designs varied, core components of the interventions were highly similar. Intervention effect results suggest that mindsets can be changed toward a growth orientation through brief GMIs, and effectiveness of GMIs on social-emotional outcomes is promising, especially in reducing depressive symptoms and aggressive reactions to perceived social exclusion. Research gaps and future directions, and implications for school psychologists and other mental health professionals are discussed. Impact Statement This is the first study to review growth mindset interventions that target social-emotional outcomes among school-aged children and adolescents. Reviews such as this are important for researchers, school psychologists and other mental health professionals, alike. For mindset researchers, it helps in conducting future empirical studies by considering empirical and methodological implications from previous intervention studies. For practitioners, it may help to design mindset interventions in more cost-effective ways that enable them to be integrated into school-based mental health prevention or intervention programs. Generally, such interventions are effective in changing youth mindset toward a growth orientation. Evidence suggests that such interventions help ameliorate depression from getting worse and reducing aggression when adolescents experience elevated social stress. Overall, growth mindset interventions show promise in improving social-emotional outcomes and cost-efficiency, especially in school settings.